PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA DAN BERFIKIR KRITIS SISWA KELAS 4 SD - Niken Bekti Utami; Firosalia Kristin; Indri Anugraheni (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2019)
This study aims to improve critical thinking skills and student learning outcomes through the application of Problem Based Learning (PBL) learning models in Grade 4 Mathematics learning. This type of research is Classroom Action Research (CAR) with two cycles. The subjects of this study were 4th grade students of SDN Randuacir 02, amounting to 25 students. Data collection techniques are carried out using tests in the form of questions and non-tests in the form of rubrics. This study uses qualitative and quantitative descriptive data analysis techniques. The results of this study indicate that there is an increase in critical thinking skills and learning outcomes of 4th grade students of SDN Randuacir 02 through application using the Problem Based Learning (PBL) learning model. This is evidenced by the increase in students' critical thinking, namely in the first cycle the average value is 58.92. Whereas, in cycle 2 there was an increase in the average value of 80.28. Experiencing an increase in the completeness of students' mathematics learning outcomes in the pre-cycle stage as many as 7 students with an average value of 55.00, then increasing in the first cycle as many as 10 students with the average score of 63.52 and increasing again in cycle 2 to 22 students with an average score of 82.00Keywords: Problem Based Learning, Critical Thinking, Learning Outcomes, Mathematics